RANCANG BANGUN APLIKASI KLASIFIKASI TINGKAT KEMATANGAN KOPI SANGRAI MELALUI CITRA DIGITAL MENGGUNAKAN ALGORITMA CNN BERBASIS ANDROID - nurhayati, yati; Gina Supratman, Sherly; Ramadhan, Muhamad Alfri (BUFFER INFORMATIKA, 2023)
In "Kopi Selamat Sore" shops there are problems in determining the level of maturity of roasted coffee because there is only 1 roaster so errors often occur in producing the level of coffee. So you need a tool that allows you to determine the level of maturity of roasted coffee precisely. The result of this research is an Android-based roasted coffee maturity level classification application. This application was created in the form of an application on an Android mobile device to make it easier for users so that they can be used whenever they want. This research uses the CNN (Convolutional Neural Network) algorithm with the CNN architecture, namely LeNet5 and the ADAM optimization function. Based on the UAT of 87.85%, it can be concluded that the application can determine the maturity level of coffee.